Green and blue water response to drought modulated by background climate and vegetation - Jing Xiao; Fubao Sun; Tingting Wang; Wang Hong (Communications Earth & Environment)
Abstract Drought affects the health of natural and socio-ecological systems by altering green water evapotranspiration and blue water runoff. However, the global patterns of green and blue water responses to drought remain unclear. Here we quantified drought using root-zone soil moisture reductions and examined the resulting water deficits across different climatic and vegetation conditions. We show that drought generally reduces both evapotranspiration and runoff globally, though with pronounced spatiotemporal variability. In high-latitude humid regions, drought can initially enhance evapotranspiration, whereas runoff responds more rapidly and declines consistently throughout drought periods. Furthermore, drought reduces runoff more than evapotranspiration in humid regions, but the reverse pattern occurs in arid regions. Compared to other vegetation types, forests exhibit smaller drought-induced reductions in evapotranspiration but greater reductions in runoff. These results underscore the importance of considering background climate and vegetation when assessing drought’s hydrological impacts, with important implications for ecohydrological understanding and water resource management.